On the Stability of Invariant Sets of Discontinuous Dynamical Systems - Perestyuk, N. A.; Chernikova, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish sufficient conditions for the stability, asymptotic stability, and instability of invariant sets of discontinuous dynamical systems.